2003
DOI: 10.1128/mcb.23.20.7230-7242.2003
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin Signals through a Transforming Growth Factor β-Like Signaling Pathway To Block Adipogenesis

Abstract: Myostatin, a transforming growth factor ␤ (TGF-␤) family member, is a potent negative regulator of skeletal muscle growth. In this study we characterized the myostatin signal transduction pathway and examined its effect on bone morphogenetic protein (BMP)-induced adipogenesis. While both BMP7 and BMP2 activated transcription from the BMP-responsive I-BRE-Lux reporter and induced adipogenic differentiation, myostatin inhibited BMP7-but not BMP2-mediated responses. To dissect the molecular mechanism of this anta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
413
1
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 514 publications
(435 citation statements)
references
References 65 publications
(102 reference statements)
13
413
1
8
Order By: Relevance
“…Receptor complex specificity can also be altered through accessory proteins such as Cripto, which suppress binding of activin to ActRII and promote nodal binding (33). In this regard, activin type II receptors are a particularly interesting example of promiscuity within this family since they participate in signal transduction for activins, myostatin, nodal, and certain bone morphogenetic proteins (BMPs) through alterations in their complex partners (15,34). Taken together, these results demonstrate that the precise composition of signaling complexes on .…”
Section: Fig 2 Representative Binding Results and Scatchard Analysimentioning
confidence: 82%
“…Receptor complex specificity can also be altered through accessory proteins such as Cripto, which suppress binding of activin to ActRII and promote nodal binding (33). In this regard, activin type II receptors are a particularly interesting example of promiscuity within this family since they participate in signal transduction for activins, myostatin, nodal, and certain bone morphogenetic proteins (BMPs) through alterations in their complex partners (15,34). Taken together, these results demonstrate that the precise composition of signaling complexes on .…”
Section: Fig 2 Representative Binding Results and Scatchard Analysimentioning
confidence: 82%
“…In vitro studies have shown that myostatin can inhibit adipocyte differentiation in 3T3-L1 mouse preadipocytes, 7 and myostatin may also inhibit Reduced body fat gain in double-muscled Mice MW Hamrick et al BMP-7 mediated adipogenesis by binding to the same receptor as BMP-7, the activin IIB receptor. 8 These data suggest that loss of myostatin function should increase adipogenesis, but the in vivo data obviously do not support this prediction. Alternatively, myostatin has been observed to promote adipogenesis in multipotential mesenchymal cells, suggesting that loss of myostatin function may directly suppress adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 93%
“…TGF-␤1 has been shown to block preadipocyte differentiation in vitro (2), and transgenic overexpression of TGF-␤1 in mice led to lipodystrophy (3). The TGF-␤ protein myostatin, also known as GDF8, has been shown to regulate adipogenesis in vitro either directly or indirectly by blocking BMP signaling (4,5). In agreement with a role in adipocyte differentiation, targeted ablation of myostatin in mice reduced accumulation of adipose tissue and weight gain in mouse models of obesity (6).…”
mentioning
confidence: 75%